Advances in Cathode Materials for High-Performance Lithium-Sulfur Batteries - Dong, Chunwei; Gao, Wang; Jin, Bo; Jiang, Qing (iScience, 2018)
Lithium-sulfur batteries (LSBs) represent a promising energy storage technology, and they show potential for next-generation high-energy systems due to their high specific capacity, abundant constitutive resources, non-toxicity, low cost, and environment friendliness. Unlike their ubiquitous lithium-ion battery counterparts, the application of LSBs is challenged by several obstacles, including short cycling life, limited sulfur loading, and severe shuttling effect of polysulfides. To make LSBs a viable technology, it is very important to design and synthesize outstanding cathode materials with novel structures and properties. In this review, we summarize recent progress in designs, preparations, structures, and properties of cathode materials for LSBs, emphasizing binary, ternary, and quaternary sulfur-based composite materials. We especially highlight the utilization of carbons to construct sulfur-based composite materials in this exciting field. An extensive discussion of the emerging challenges and possible future research directions for cathode materials for LSBs is provided. [Display omitted] Inorganic Chemistry; Electrochemical Energy Storage; Energy Materials